CCAFS Climate datasets map - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
GCM Portal - CCAFS Climate datasets map. The datasets contained in this website are part of the International Centre for Tropical Agriculture (CIAT) and The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).